PARTISIPASI PEREMPUAN PADA PENERAPAN AGROFORESTRI DI DESA WAREMBUNGAN KECAMATAN PINELENG - Sitti S. Umagap; Semuel P. Ratag; Hengki D. Walangitan (Universitas Sam Ratulangi, 2016)
ABSTRACTWoman Participation in the Implementation of Agroforestry in the Village of Warembungan, sub-District of PinelengIt is well known that woman has certain participation level varied from household activities to a broader sense such as participation in household income generating. With the exception to woman monthly income that valued in rupiahs, it is very rarely that contribution value of woman participation is quantified. This is happened to all woman community at city and village level as well. At village level, where farming effort ast as prime mover of household economy, it is estimated that the smaller the number of family member, the higher the participation level of woman contribution in farming activities. Warembungan Village, Subdistrict Pineleng is a sample of village where the farming effort in form of agroforestry applied to fulfill the family needs. It is therefore, woman participation level in order to establish its contribution value needs to be quantified. This study aimed to describe the level of woman participation in agroforestry activities, and to further analyze the relation between woman participation and socio-economy factors. Research was conducted in Warembungan Village, subdistrict Pineleng using structured questioner survey analyzed descriptively and then using Chi-square (x2) to see the relation mentioned above. Results showed that the level of participation of women classified as medium category with a percentage of 80%, The female participation rates no significant correlation with socio-economic factors,Keywords: woman participation, Warembungan, socio-economy factors